Analysis Of Artificial Signals Of CPS, Spark Timing, And Fuel Injection Timing Toward The Engine Behaviour - Jafri, Muhammad Nabil Asyraf (Universiti Sains Malaysia, 2018)
Internal combustion (IC) engine is widely used in automotive. The mainstream engine that can be found in any automotive is spark ignition (SI) engine with four stroke cycle. The growth of electronic device in engine system is increased throughout the time. Mechanical system inside the engine system slowly being replaced by the electronic system. Engine control unit (ECU) is a device that being used to control all the engine parameters whether it for is spark, fuel, speed, and other applications. ECU plays a vital role on how the engine performs. Engine knock is the major concern in the engine system. This phenomenon occurs due to an incomplete combustion inside the combustion chamber. Engine knock is a defect that may lead to less efficiency of the engine performance and damage to the engine components. This defect can be controlled by altering the spark timing or adjusting the fuel injection timing. This research is carried out with the aims to analyse the artificial signals of CPS and spark toward the engine behaviour and to study the fuel injection timing toward the knocking phenomenon. A test bed for the Modenas GT128 engine is fabricated and it is mounted onto the go-kart chassis. By using the microcontroller, a programmable code is used to generate the artificial signals and the signals will be analysed. The results show that the artificial signal is capable to alter the engine behaviour. Engine knock is possible to occur at idling speed and also at high speed operating condition.